Sequencing and analysis of the complete mitochondrial genome of Gloydius saxatilis (Squamata: Viperidae: Crotalinae). (3rd July 2016) - Xu, Chunzhu; Xie, Fei; Liu, Yichen; Zhao, Shuai; Wang, Yongsheng; Ma, Teng; Zhao, Tianqing
Abstract: The mitochondrial genome sequence of Gloydius saxatilis is analyzed and presented for the public for the first time. The genome was 17, 218 bp in length and contained 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes and 2 control regions. The overall base composition was A (32.3%), C (28.9%), T (25.8%), and G (13.0%). The base compositions presented clearly the A-C skew, which was most obviously in the protein-coding genes. The extended termination-associated sequence domain, the central conserved domain and the conserved sequence block domain are defined in the mitochondrial genome control region of G. saxatilis . Mitochondrial genomes analyses based on MP, ML, NJ and Bayesian analyses yielded identical phylogenetic trees, indicating a close phylogenetic affinity of the thirteen Crotalinae species. It appeared that no less than two major phyletic lineages were present in Crotalinae. The main clades within the Crotalinae supported are: A clade including the Protobothrops. A clade ( G. brevicaudus, G. ussuriensis, G. intermedius, G. saxatilis) with the Ovophis as the sister taxon to Protobothrops and was supported by bootstrap values of 88%. The four Gloydius species formed a paraphyletic group with the high bootstrap value (100%) in all examinations.